High efficacy of sofosbuvir/velpatasvir and impact of baseline resistance‐associated substitutions in hepatitis C genotype 3 infection. Issue 9 (14th March 2018) - von Felden, J.; Vermehren, J.; Ingiliz, P.; Mauss, S.; Lutz, T.; Simon, K. G.; Busch, H. W.; Baumgarten, A.; Schewe, K.; Hueppe, D.; Boesecke, C.; Rockstroh, J. K.; et al.
Summary: Background: Twelve weeks of the pangenotypic direct‐acting antiviral (DAA) combination sofosbuvir/velpatasvir (SOF/VEL) was highly efficient in patients with hepatitis C virus (HCV) genotype 3 (GT3) infection in the ASTRAL‐3 approval study. However, presence of resistance‐associated substitutions (RASs) in the HCV nonstructural protein 5A (NS5A) was associated with lower treatment response. Aim: To assess the efficacy and safety of SOF/VEL ± ribavirin (RBV) and the impact of NS5A RASs and RBV use on treatment outcome in HCV GT3 infection in a real‐world setting. Methods: In this multicentre cohort study, GT3 patients from ten treatment centres across Germany were included. Sustained virological response was assessed 12 weeks after end‐of‐treatment (SVR12) in modified intention‐to‐treat (mITT) and per‐protocol analysis (PP). NS5A RASs were tested by population‐based sequencing. Results: A total of 293 GT3 patients were included. The median age was 48 years, 70% were male, 25.3% were cirrhotic, 9.2% were HCV/HIV co‐infected and 21.8% were treatment‐experienced, including 4.1% with DAA experience. Baseline NS5A RASs (Y93H, A30K, L31M) were detected in 11.2%. RBV was added in 5% of noncirrhotic and 58.9% of cirrhotic patients, respectively. SVR12 rates for SOF/VEL±RBV were 95.9% (mITT) and 99.5% (PP), respectively. Only 1 virological relapse occurred in a cirrhotic patient previously treated with SOF/RBV. No treatment‐related major adverse events occurred. Conclusion: Twelve weeks of SOL/VEL±RBV was safe and highly efficient in HCV GT3 across a diverse patient population. Baseline NS5A RASs were rarely observed and presence did not seem to impact SVR, regardless of the use of RBV. Abstract : Linked Content This article is linked to Sadler and von Felden et al papers. To view these articles visithttps://doi.org/10.1111/apt.14646 andhttps://doi.org/10.1111/apt.14648 .